Comparative Histological and Histochemical Studies on Retina of Sheep and Goat - S. Rajathi, (Indian Journal of Veterinary Anatomy, 2022)
The present study was conducted on eye ball of six from each apparently healthy young and adult sheepand goat. Micrometric parameters namely total thickness and thickness of various layers of central and peripheralretina were measured in young and adult sheep and goat. The sensory part of the retina was composed of ten layersnamely retinal pigmented epithelium (RPE), layer of rods and cones, external limiting membrane, outer nuclearlayer, outer plexiform layer, inner nuclear layer, inner plexiform layer, ganglion cell layer, nerve fiber layer andInternal limiting membrane in both young and adult sheep and goat. Ganglion cell layer showed prominent largeblood vessels and large proportion of large sized ganglion cells in young sheep and goat when compared to adultanimals. Retina was thick at optic disc (Central) region and thin towards the ora ciliaris retinae. The micrometricalmean values of the total thickness of retina, thickness of various layers of central and peripheral retina amongyoung and adult sheep and goat did not show significant difference at 5 % level. Glial Fibrillary Acidic Protein(GFAP) antibody expression of Muller's cells was found in the inner plexiform layer and strong positivity wasfound in the ganglion cell layer in both young and adult sheep and goat.